2021
DOI: 10.1080/14017431.2021.1927171
|View full text |Cite
|
Sign up to set email alerts
|

Low risk patients with acute atrial fibrillation and elevated high-sensitivity troponin do not have increased incidence of pathological stress tests

Abstract: Objectives: Many patients with atrial fibrillation (AF) or atrial flutter (AFL) and rapid ventricular response (RVR) have elevated high-sensitivity troponin T (hsTnT) values. Elevated hsTnT is an independent risk marker for cardiovascular events and mortality. The aim was to examine if AF/AFL patients with RVR and elevated hsTnT have an increased incidence of pathological cardiac stress tests, indicating need of further evaluation for coronary artery disease (CAD). Design: We prospectively included 90 AF/AFL p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…The optimal cutoff HS-cTnT value (30 ng/l) was determined to be above the 99th percentile upper reference limit value (14 ng/l), suggesting that minor HS-cTnT elevations in new-onset AF may not necessarily reflect underlying clinically significant CAD, but rather may be precipitated by common confounders such as tachycardia, renal impairment, acute heart failure, and infection. This is consistent with a study by Thelin et al [11], who found that low-risk patients with rapid paroxysmal AF/ AFL but minor HS-cTnT elevations (median, 25; IQR, 18-35 ng/l) did not have an increased incidence of pathological stress tests compared with those with a normal troponin.…”
Section: The Main Results Were As Followssupporting
confidence: 92%
See 2 more Smart Citations
“…The optimal cutoff HS-cTnT value (30 ng/l) was determined to be above the 99th percentile upper reference limit value (14 ng/l), suggesting that minor HS-cTnT elevations in new-onset AF may not necessarily reflect underlying clinically significant CAD, but rather may be precipitated by common confounders such as tachycardia, renal impairment, acute heart failure, and infection. This is consistent with a study by Thelin et al [11], who found that low-risk patients with rapid paroxysmal AF/ AFL but minor HS-cTnT elevations (median, 25; IQR, 18-35 ng/l) did not have an increased incidence of pathological stress tests compared with those with a normal troponin.…”
Section: The Main Results Were As Followssupporting
confidence: 92%
“…This is consistent with a study by Thelin et al . [11], who found that low-risk patients with rapid paroxysmal AF/AFL but minor HS-cTnT elevations (median, 25; IQR, 18–35 ng/l) did not have an increased incidence of pathological stress tests compared with those with a normal troponin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation